RELATIONSHIP BETWEEN ASPECTS OF RELIGION AND WORK-FAMILY INTERFACE IN MALAYSIA : A LONGITUDINAL STUDY - Zaiton, Hassan; Dayang Kartini, Abang Ibrahim; Nik Norsyamimi, Md Nor; Surena, Sabil; Nur Fatihah, Abdullah Bandar (International Journal of Business and Society, 2017)
Shifting from Western-dominated perspectives, this study aimed to investigate relationship between religion and work-family conflict and enrichment. SPSS analysis was conducted on data obtained through two selfreport questionnaires completed three months apart by 296 executives and non-executives from six public and private sector organizations in Kuching, Sarawak. After controlling for conflict and enrichment at Time 1, aspects of religion (importance of religion and perception of religiousness) negatively related with workfamily conflict and positively associated with work-family enrichment. The study underscores the roles religion, which have been neglected in Western studies, as important parts in shaping the work-family interface in Malaysia. Therefore, organizations should include religious activities to encourage work-life balance among employees